2020
DOI: 10.1016/j.jfs.2020.100724
|View full text |Cite
|
Sign up to set email alerts
|

Macroprudential policy and bank systemic risk

Abstract: This paper investigates the effectiveness of macroprudential policy to contain the systemic risk of European banks between 2000 and 2017. We use a new database (MaPPED) collected by experts at the ECB and national central banks with narrative information on a broad range of instruments which are tracked over their life cycle. Using a dynamic panel framework at a monthly frequency enables us to assess the impact of macroprudential tools and their design on the banks' systemic risk both in the short and the long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(46 citation statements)
references
References 51 publications
4
40
0
2
Order By: Relevance
“…Dutta and Saha (2020) found that macroprudential policy were able to minimize financial risk exposure even though it was more effective during normal condition than financial turmoil. This finding is also in line with Meuleman and Vennet (2020), Esteban et al, (2020), Thi and Anh (2019) and Zhang et al, (2018) who also found that macroprudential policy lessened the bank's individual risk over the observation period.…”
Section: Table 1 Marcroprudential Policy Instrument In Indonesiasupporting
confidence: 87%
“…Dutta and Saha (2020) found that macroprudential policy were able to minimize financial risk exposure even though it was more effective during normal condition than financial turmoil. This finding is also in line with Meuleman and Vennet (2020), Esteban et al, (2020), Thi and Anh (2019) and Zhang et al, (2018) who also found that macroprudential policy lessened the bank's individual risk over the observation period.…”
Section: Table 1 Marcroprudential Policy Instrument In Indonesiasupporting
confidence: 87%
“…Counterfactual simulations indicate that, if the countries had not used any macroprudential policy measures in the period 2011-2013, the bank credit growth, housing credit growth and house price appreciation would have been substantially higher. Similarly, Meuleman and Vander Vennet (2020) demonstrate that the macroprudential policy instruments reduce individual bank risks, as well as bank systemic risk, as assessed by stock market investors. The latter is an important finding because reducing systemic risk is the key goal of macroprudential policies.…”
mentioning
confidence: 88%
“…The results show that the primary channel behind this relation is reduced leverage, but lower portfolio risk also plays a role. Meuleman and Vennet (2020) investigate the effectiveness of macroprudential policy to determine systemic risk in the short and long run. The systemic risk criteria are decomposed into an individual bank risk component and a systemic linkage component.…”
Section: Literature Reviewmentioning
confidence: 99%